Risk Indicators and Treatment Needs of Children 2-5 Years of Age Receiving Dental Treatment under General Anesthesia in Saskatchewan - Alyssa Weninger; Erica Seebach; Jordyn Broz; Carol Nagle; Jessica Lieffers; Petros Papagerakis; Keith Da Silva (MDPI AG, 2022)
Background: When compared to national averages in Canada, Saskatchewan has one of the highest rates of dental treatment under general anesthesia (GA) and average costs per child. Thus, the purpose of this cross-sectional study is to explore the risk indicators and treatment needs of children receiving dental treatment under GA in Saskatchewan. Methods: In this cross-sectional study, we recruited caregivers of children between 24 and 71 months of age in Saskatoon, Canada. Caregivers completed a 40-item questionnaire, which was supplemented with clinical data and then subject to statistical analysis (independent t-tests and one-way ANOVA). Results: A total of 90 caregiver/child dyads were enrolled with the mean age for children being 49.5 ± 12.3 months. The mean age of a child's first dental visit was 34.7 ± 15.3 months with only 37.9% of children having a dental home. The mean deft index was 11.7 ± 3.4, with an average of 10.9 ± 3.5 teeth receiving treatment. Additionally, location of primary residence (p = 0.03), family income (p = 0.04), family size (p = 0.01), parental education (p = 0.03), dental home (p = 0.04), and body mass index (p = 0.04) had a statistically significant association with a higher mean deft. Conclusions: Our cross-sectional study confirms that children who require dental treatment under GA have a high burden of disease. While individual risk indicators such as diet and oral hygiene play a role in the progression of early childhood caries (ECC), we also demonstrate that children who do not have access to early preventive visits or a dental home are at a higher risk. In addition to improving motivation for oral hygiene at home and nutritional education, improving access to oral health care should be addressed in strategies to reduce ECC.